The level of scientific competencies of teachers of persons with intellectual disabilities (light and medium)- field study at the Psychological Educational Center for the mentally handicapped – Tamezguida Medea - Badri , Mohamed; Hamoud , Taha (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2024)
The issue of scientific competencies among special education teachers is an issue of great importance as it determines the extent of the teacher’s cognitive, emotional and behavioral preparations, which qualify him to be at the level of care and care for a mentally disabled child who suffers from deficiencies in various areas of life and who is in dire need of social rehabilitation that will enable him to integrate naturally and effectively into the environment. His peers, and relieves him of some of that suffering. Any deficiency or decrease in the level of competencies of the teacher will negatively affect the mentally disabled child and deprive him of the opportunity for social integration. This is something that specialists attach great importance to because of its benefits and benefits that bring positive results to the individual and society. Our current study aims to know the level of scientific competencies among teachers of people with mental disabilities (mild and moderate) and to investigate the possibility of statistically significant differences in these levels according to the variables of gender, scientific specialization and field experience, which led the researcher to rely on the descriptive analytical approach.